Peran Pendidikan Islam dalam Membentuk Karakter Siswa Sekolah Dasar: Kajian Literatur - Rani Lestari (Medan Resource Center, 2024)
Islamic education plays a strategic role in shaping students' character through moral, ethical, and spiritual values derived from the Qur'an and Hadith. Amid the challenges of globalization, Islamic education serves not only as a medium for knowledge transmission but also as a foundation for developing individuals with strong moral integrity, social responsibility, and religious awareness. This study aims to examine the contribution of Islamic education systems, both formal and non-formal, to students' character development. The study employed a literature review approach by analyzing 35 scholarly sources, consisting of journal articles, books, and relevant educational documents published on Islamic education and character formation. The analysis indicates that the integration of Islamic values into curriculum implementation, learning activities, role modeling, and school culture contributes significantly to the development of honesty, discipline, responsibility, empathy, and social awareness among students. The review further reveals that character formation becomes more effective when supported by collaborative engagement among families, educational institutions, and communities. This study contributes to the development of Islamic education by providing a comprehensive synthesis of strategies for strengthening character education and highlighting the importance of holistic value integration in addressing contemporary educational challenges.